Slamming analysis of skips in mine shafts: the effect of secondary stiffening in the guides - D'Arcy, Evans A (Department of Mechanical Engineering, 2016)
Previous investigations into the dynamics of skips in deep mine shafts have led to the identification of slamming as a phenomenon that results in exceptionally high forces in the shaft steelwork and conveyance. Slamming may occur when the rollers on the skip, that normally act on the guide, fail. Possible damage caused to the shaft steelwork, as a result of slamming, limits the hoisting speed of the skip. This study extends previous work by investigating the effect of secondary stiffening, due to axial tension effects as the guide deforms, on the slamming response of the skip. A mathematical model of a single slamming event is formulated and a numerical solution procedure presented. A number of computer simulations, including parametric studies, are presented. An important conclusion is that previous slamming models were shown to predict a reduced response when low axial compressive forces are present in the guides while predicting an increased response for high (near the buckling load) axial compressive forces. The inclusion of secondary stiffening; due to axial tension effects, thus represents a significant refinement of the slamming model.